Aging effect of Aloe vera (L.) Burm. f. on tyrosinase inhibitory and antioxidant activities - Chailap, Benjamat; Nuanyai, Thanesuan (วารสารวิทยาศาสตร์และเทคโนโลยี หัวเฉียวเฉลิมพระเกียรติ, 2022)
Aloe vera (L.) Burm. f. (Aloe barbadensis Mill.) extract is an essential ingredient in a wide variety of cosmetic products. This research compares the antioxidant activity and tyrosinase inhibitors of A. vera extracted from leaves at different stages. The results could be applied in arranging A. vera leaf into grades for the cosmetic field. In this study, three stages of A. vera leaf: A1 (4-6 months), A2 (7-9 months), and A3 (10-12 months) were divided. In extraction processes, A. vera leaf samples were peeled and rinsed with deionized water. After A. vera gel was blended thoroughly and freeze-dried, A. vera powder was obtained. The results showed that the water content of A. vera leaf at A1, A2, and A3 were 98.00 ± 0.02%, 97.10 ± 0.02%, and 96.00 ± 0.04%, respectively. A. vera powder was extracted with 80% v/v methanol and dried by vacuum rotary evaporator. The extract yields of all three stages (A1-A3) were 24.97 ± 0.28%, 35.27 ± 0.70%, and 32.20 ± 0.29%, respectively. The antioxidant activity of methanol crude extracts was examined by using DPPH and ABTS techniques with Trolox as the standard. The samples (A1-A3) and standard Trolox showed the antioxidant activity against the DPPH radical in terms of percent inhibition at 41.76 ± 0.57%, 40.72 ± 2.31%, 37.01 ± 2.22%, and 49.90 ± 1.74%, respectively. The samples (A1-A3) and standard Trolox showed the antioxidant activity against the ABTS•+ radical in term of percent inhibition at 13.65 ± 3.44%, 53.02 ± 1.16%, 13.85 ± 1.08%, and 74.88 ± 2.15%, respectively. Among A. vera extracts from all three stages, the A2 showed the highest antioxidant activity derived from ABTS technique. Tyrosinase inhibition of A. vera extracts (A1-A3) was investigated and compared with standardized kojic acid at the concentration of 50 ug/mL. We found that A. vera extracted from A2 showed the highest tyrosinase inhibition at 18.68 ± 0.99%, while A. vera A1, A2 stages, and the kojic acid showed tyrosinase inhibition at 17.93 ± 0.80%, 15.74 ± 1.17%, and 13.03 ± 0.96%, respectively. The results showed that gel extract from A. vera at age 7-9 months had an antioxidant activity and tyrosinase inhibition suitable for cosmetic application.